IMPLEMENTASI PAIKEM PENGARUHNYA TERHADAP KOMPETENSI, KUALITAS, EFISIENSI DAN EFEKTIVITAS PEMBELAJARAN - Indrayati, Indrayati (Media Mahardhika, 2019)
The research aimed at developing and implementing the PAIKEM method with Student centered learning, Project Based Learningand cooperative learning, effective learning, fun Learningso the learning in the accounting department  able to produce high quality human resources so able to compete  in the global  or international market. The research method was quantitative with data collection by using interview, questionnaire, documentation, triangulation from class room action  research.  Analysis method done with Manova to know the influence of the Paikem method implementation toward competence, quality, efficiency, and effectiveness of learning. The results showed that student centered learning, cooperative learning, fun learning influence insignificantly toward learning competence, while project based learning, creative learning, effective learning influence significantly toward learning competence.  Then student centered learning, cooperative learning, fun learning influence insignificantly toward learning quality, while project based learning, creative learning, effective learning influence significantly to the learning quality.  Then student centered learning, creative learning influence insignificantly toward the learning efficiency, while project based learning, cooperative learning, effective learning influence significantly toward learning efficiency. Toward learning efficiency.  Then student centered learning,  creative learning, effective learning influence insignificantly toward learning effectiveness, while project based learning, cooperative learning, fun learning influence significantly toward learning effectiveness.